Implementasi program RALINA dalam meningkatkan minat dan partisipasi literasi masyarakat Provinsi Jawa Tengah - Liya Yusrina Sabila; Nurul Hidayati; Rochimatun Rochimatun; Annisa Nurul Hikmah (Penamas: Journal of Community Service, 2026)
The RALINA Program (Rumah Literasi Nasyiatul Aisyiyah) is a flagship program of the Regional Leadership Board of Nasyiatul Aisyiyah (PWNA) Central Java aimed at improving community-based literacy. This community service study aims to describe the implementation and impact of RALINA on reading interest and community participation. The method used was descriptive quantitative and qualitative, involving 18 program managers as respondents. The results showed that RALINA had a positive impact on reading interest (94.4% of respondents stated it had an impact/very impactful) and was effective in reaching various age groups (94.4% stated effective/very effective), especially children. Public enthusiasm for borrowing services and read-aloud programs was high. Active community participation in independently supporting the program also began to develop (88.8% participated/very participated). However, the frequency of flagship programs and regular visitor participation varied and was not yet optimal due to limited facilities and management consistency. The RALINA program has succeeded in fostering a community-based literacy ecosystem and has the potential to be developed into an inclusive and sustainable literacy center.